The Contemporary Construction of the Chinese Form of Marxist Literary Criticism - Hu, Yamin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
This open access book is the first comprehensive and systematic study of Chinese Marxist literary criticism as an independent theoretical form. It discusses and describes the theoretical features of the Chinese form of Marxist literary criticism by refining and re-interpreting the iconic key concepts of (3z(Bpeople,(3y z(Bnation,(3y z(Bpolitics,(3y z(Bpraxis,(3y (Balong with the relationships between literature, technology and capital. Literary criticism and value judgment has also been discussed at length with insightful and valuable views being provided. This book is a brilliant introduction to the topic and ideal academic material for global readers to grasp the essence of Chinese Marxist literary critical thought. Yamin Hu is Professor at Central China Normal University. She is one of the leading Chinese scholars in the areas of Marxist literary theory studies, literary criticism, comparative literature and narrative studies. She is the rare female pioneer who strived to forge herway in Chinese academia and acquired a strong reputation as early as the 1990s. She has hosted a number of national-level funding programs, including two Major Projects of the National Social Science Fund. Her publications include over 12 monographs, textbooks, translations, and more than 100 academic articles. Her textbook Comparative Literature which received the National Excellent Teaching Material Award has been translated into Vietnamese. Professor Yamin Hu also edited the book Keywords in Western Literary Criticism and Contemporary China (Vol.1&2) in 2020. .s
Chapter 1: Introduction -- Chapter 2: People: The Starting Point & the Destination of Literary Criticism -- Chapter 3: Nation: A New Dimension of Literary Criticism in the Context of Globalization -- Chapter 4: The Political Dimension of Literary Criticism -- Chapter 5: The Praxis Dimension of Literary Criticism -- Chapter 6: Marxist Literary Criticism in the Hi-Tech Era -- Chapter 7: Literature and Capital in a Market Economy -- Chapter 8: A Study of Value Judgment -- Chapter 9: Conclusion.
Keywords: Literature -- History and criticism; Marxian economics; China -- History; Social policy; Ontology; Aesthetics; Literary Criticism; Marxist Economics; History of China; Social Policy; Ontology; Aesthetics